Contact-dependent disruption of the host cell membrane skeleton induced by Trichomonas vaginalis. - Fiori, P L (1997)
This report presents evidence showing that the pathogenetic process of the protozoan parasite Trichomonas vaginalis involves degradation of the target cell membrane skeleton; spectrin, the most representative protein within this structure, has been identified as the main molecular target. Degradation of the target cell spectrin is accomplished only upon contact with the parasite, and immunochemical and immunofluorescence studies performed with the erythrocyte as a model demonstrate that degradation of the protein takes place before target cell lysis. A preliminary characterization of the effectors involved has led to the identification of a nonsecreted 30-kDa proteinase which is characterized by a high specificity for spectrin. This molecule is suggested as the main effector responsible for cytoskeletal disruption.